Hubungan Perilaku Fear of Missing Out dengan Self Esteem Terhadap Mahasiswa Bimbingan dan Konseling di Universitas Islam Negeri Mahmud Yunus Batusangkar : Indonesia - olfakhrina7, olfakhrina7 (EPIK: Edukasi Penerapan Ilmu Konseling, 2025)
Fear of Missing Out is an individual’s fear and concern about missing out on something fun and feeling connected to others. Fear of Missing Out can affect a person’s Self Esteem. Self-Esteem is a self assessment that is influenced by attitudes, interactions, appreciation, and acceptance of others towards individuals. The problem discussed in the research is about "Fear of Missing Out Behavior with Self-Esteem for Guidance and Counseling Students at Mahmud Yunnan State Islamic University" at Mahmud Yunus State Islamic University Batusangkar". The purpose of this study was to determine whether there is a relationship between the behavior of Fear of Missing Out behavior with Self-Esteem towards Guidance and Counseling students at Mahmud Yunus Batusangkar State Islamic University. Mahmud Yunus Batusangkar State Islamic University. The research method used is quantitative method with correlational research type, sampling using probability sampling technique with Slovin’s formula of 108 students so that the research sample amounted to 84 students. Instrument validity test using product moment correlation and normality test, data homogeneity test and linearity test. Based on the research results obtained Sig value. (2-tailed) 0.000 <0.05, so it can be concluded that the hypothesis Ha is accepted Ho is rejected, which states that there is a significant relationship between Fear of Missing Out and Self-Esteem of Guidance and Counseling students at Mahmud Yunus State Islamic University Batusangkar. Keywords: Fear of Missing Out, Behavior, Self-esteem.